2018
DOI: 10.1142/s0218488518500186
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Uncertainty Handling Techniques in Smart Grid

Abstract: This paper is a review of uncertainty modeling techniques used in smart grid studies. The literature dealing with uncertainty from various sources in smart grid is analyzed and presented. In a modern power grid, the risk may arise due to different reasons; in-termittent renewable energy sources, uncertain consumer reactions on demand response, driving patterns of electric vehicles, etc. The paper has two objectives. First is to bring out the trends in uncertainty handling techniques used in electrical power sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 93 publications
0
6
0
1
Order By: Relevance
“…These uncertainties make the exact prediction or forecast of generation and consumption difficult, thus affecting the reliability and security of the power system. It has been analyzed that there are two types of uncertain parameter, namely, technical parameters and economic parameters . Technical parameters are further classified as operational parameters and topological parameters.…”
Section: Factors To Be Considered For Ems Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…These uncertainties make the exact prediction or forecast of generation and consumption difficult, thus affecting the reliability and security of the power system. It has been analyzed that there are two types of uncertain parameter, namely, technical parameters and economic parameters . Technical parameters are further classified as operational parameters and topological parameters.…”
Section: Factors To Be Considered For Ems Implementationmentioning
confidence: 99%
“…It has been analyzed that there are two types of uncertain parameter, namely, technical parameters and economic parameters. 139 Technical parameters are further classified as operational parameters and topological parameters. Operational parameters include the information of demand and renewable generation, and topological parameters include the information about the disruption of any line or generating unit.…”
Section: Uncertainty Management Techniquesmentioning
confidence: 99%
“…13 This controller can either be an aggregator or an utility, that gathers all information, like energy consumption pattern of the load/consumer, energy production of the DER, and so forth, of each node to run optimization programs toward achieving their goals, for an effective operation. 14 In this area, contributions focus on how solar and wind energy could contribute to the large-scale use, and also on the potential of demand-responsive flexible loads (DR). As an example, for energy systems including large-scale wind energy, a new optimal planning method considering DR is proposed.…”
Section: Energy Management Systemmentioning
confidence: 99%
“…Several approaches have been proposed to handling the uncertainties in the electric power system, and they can be generally classified into robust optimization approaches, probabilistic approaches and interval -set analysis. An updated review of numerous recent approaches can be found in [37,38]. Robust optimization approaches model uncertainties as intervals and involve optimization problems to solve state boundaries.…”
Section: Modeling Of Uncertaintiesmentioning
confidence: 99%